A series of tricarbonylrhenium(I) complexes with the N-methyl-2-pyridinecarboxyamide ligand: Synthesis, structure, spectroscopic characterization and computational studies. (17th February 2015) - Lyczko, Krzysztof; Lyczko, Monika; Mieczkowski, Józef
Graphical abstract: Synthesis, structure and characterization of neutral and cationic tricarbonylrhenium(I) complexes in a '2 + 1' system with the bidentate ligand N -methyl-2-pyridinecarboxyamide and with one monodentate ligand, being either an anion (Cl, Br, I and SCN) or a neutral molecule (imidazole (Him) and 3, 5-dimethylpyrazole (Hdmpz)), are presented. Flexidentate behavior of the N -methyl-2-pyridinecarboxyamide ligand is also shown. Abstract: The syntheses and structures of seven new tricarbonyl complexes of rhenium(I) in the '2 + 1' system with the bidentate ligand N -methyl-2-pyridinecarboxyamide (NC5 H4 -CO-NH-CH3, LH (Me) ) and one monodentate ligand, being either an anion (Br, I or SCN) or a neutral molecule (imidazole (Him) or 3, 5-dimethylpyrazole (Hdmpz)), have been presented. In addition, the structure of the [Re(CO)3 (LH (Me) NO )Cl] complex (1 ) was re-determined at low temperature and compared with similar structures containing other halide ions. The use of mixed ligands leads to the formation of neutral or cationic (in the form of PF6 − salts) tricarbonylrhenium(I) complexes: [Re(CO)3 (LH (Me) NO )X] (X = Cl, Br, I, NCS) (complexes1 –4 ) and [Re(CO)3 (L (Me) NN )Y] (Y = Him, Hdmpz) (5 and6 ) or [Re(CO)3 (LH (Me) NO )Y] + (7 and8 ), respectively. Structures of the obtained complexes also show possible flexidentate behavior of the N -methyl-2-pyridinecarboxyamide ligand, which coordinates as a neutral N, O -donor in complexes1 –4, 7 and8 or as an anionic N, N -donor in5 and6 . Crystal structures of all the complexes were determined by means of single-crystal X-ray diffraction and the results were compared with the molecular structures obtained from DFT calculations. The compounds were characterized by FT-IR, NMR and UV–Vis techniques. IR and UV–Vis spectra were also simulated by DFT and TD-DFT methods.